Study of rheological behaviour of polymer melt in micro injection moulding with a miniaturized parallel plate rheometer. (April 2021) - Trotta, G.; Stampone, B.; Fassi, I.; Tricarico, L.
Abstract: The study of the rheological behaviour of the polymer in micro cavities is one of the aspects related to the technology of micro injection moulding (μIM) still substantially unresolved. Even today, there are no databases on the rheological characteristics of the material specific for the μIM, which, therefore, takes into account a number of important differences compared to the conventional injection moulding. In this paper, the study of the rheological behaviour of the polymer melt in a thin plate cavity with variable thickness has been conducted. The use of a micro injection moulding machine, on which the prototype of a sensorized mould with pressure and temperature sensor has been mounted, allowed the rheological study of the material under high shear rate conditions. After preliminary tests on different thicknesses, it has been studied the viscosity of polymer melt for 400 μm thickness. The viscosity reduction observed meets the characteristics of a pseudoplastic fluid subject to shear thinning and the wall slip seems to play an important role in the apparent reduction of viscosity. The results suggest to increase injection speed, and consequently injection pressures, so that the reduced viscosity can help melt flow to overcome the extreme conditions due to the aspect ratio and to obtain greater efficiency from the filling phase against the high cooling rate typical of micro injection moulding. Highlights: The preliminary tests revealed that 100 μm thickness is the technological limit for micro injection moulding of thin plates. The study clearly evidenced a viscosity reduction at high shear stress and therefore linked to the filling phase. The main contribution to apparent viscosity reduction is mainly attributed to the wall slip.